2022
DOI: 10.3389/fsurg.2022.1005860
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with uniportal robotic thoracic surgery lobectomy

Abstract: BackgroundInvasiveness is considered one of the cornerstones of every field of surgery, and video-assisted thoracoscopic (VATS) approaches are now routinely used worldwide to perform pulmonary resections. Recently, robotic-assisted thoracic surgery (RATS) has become the preferred technique in many centers; it is routinely performed using three or four ports with at least one service incision, contrasting with the real concept of invasiveness, especially when compared to uniportal VATS (U-VATS). Hereby, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…When compared to hybrid uniportal robotic-assisted approach, we consider that our technique resolves the need to rely on the assistant for the critical steps of the surgery such as stapling and, mirroring the uniportal VATS approach, makes for a faster learning curve. Already the technique has gained interest, and similar results in terms of safety and surgical outcomes have been reported (17). The robotic approach has proven to be less invasive (18), thus allowing for a shorter hospital stay, and in our comparative groups, patients that underwent a uniportal approach had a faster discharge from hospital.…”
Section: Complex Resectionssupporting
confidence: 56%
“…When compared to hybrid uniportal robotic-assisted approach, we consider that our technique resolves the need to rely on the assistant for the critical steps of the surgery such as stapling and, mirroring the uniportal VATS approach, makes for a faster learning curve. Already the technique has gained interest, and similar results in terms of safety and surgical outcomes have been reported (17). The robotic approach has proven to be less invasive (18), thus allowing for a shorter hospital stay, and in our comparative groups, patients that underwent a uniportal approach had a faster discharge from hospital.…”
Section: Complex Resectionssupporting
confidence: 56%
“…The former is already coming true as the monopoly of the only RATS system manufacturer is coming to an end, and alternative, cheaper RATS systems are now emerging on the marketplace. The latter may also be coming true as an intrepid handful of surgeons have begun to experiment with a URATS approach for various types of lung resections, using a single intercostal incision, without rib spreading (62)(63)(64)(65). A robotic camera, robotic dissecting instruments and robotic staplers are used, without the need of a bedside assistant to handle any conventional VATS staplers and instruments (63,64).…”
Section: Multi-modality Therapymentioning
confidence: 99%
“…At the time of this writing, all that the world knows is that a very small number of surgeons have performed an unspecified number of URATS operations (62)(63)(64). To date, only one group has reported a series of 24 URATS lung resections without mortality (65). There is as yet no further consistent documentation of the overall safety of the approach.…”
Section: Multi-modality Therapymentioning
confidence: 99%
“…A total of 137 studies on the application of u-RATS were identified for inclusion, with 12 progressing to inclusion (5 cohort series, 7 case reports) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The cohort series are presented in Table 3.…”
Section: Study Characteristics and Baseline Demographic Data (See Tab...mentioning
confidence: 99%